Clinical and sleep-related characteristics as predictors for risk of dysphagia in patients with chronic obstructive pulmonary disease (Revista Contexto & Saúde, 2025)
Objective: To identify clinical risk predictors for dysphagia in patients with chronic obstructive pulmonary disease (COPD). Methods: This is a cross-sectional study carried out in the pulmonary rehabilitation unit of a University Hospital. The sample included 37 COPD patients, of both sexes, in ambulatory follow-up. Patients were evaluated in relation to aspects of body composition, peak expiratory flow, perception of dyspnea (Modified Medical Research Council - mMRC), impact of the disease on health status (COPD Assessment Test - CAT), excessive daytime sleepiness (Epworth Sleepiness Scale - ESS), risk of sleep apnea (Berlin Clinical Questionnaire), modified Mallampati index and symptoms indicative of dysphagia (Questionnaire for Dysphagia Screening - QDS). Data were analyzed using multivariate analysis and the level of significance was set at 5%, with a confidence interval of 95%. Results: In a sample of patients with moderate to severe COPD, 83% reported symptoms of swallowing dysfunction assessed by the QDS and 62.2% presented risk for sleep apnea. The CAT, Epworth and Berlin indices predicted 32% of risk for dysphagia. Conclusion: The impact of the disease on health status, daytime sleepiness scores and risk of sleep apnea were the best predictors for risk of dysphagia for COPD among those surveyed. In this sense, it is proposed that assessments of health status, sleepiness and QDS be included in the routine assessment of COPD patients.